Milady standard cosmetology - Frangie, Catherine M.; Botero, Alisha Rimando; Hennessey, Colleen; Lees, Mark; Sanford, Bonnie; Shipman, Frank; Wurdinger, Victoria; Milady Publishing Company (Clifton Park, NY : Cengage Learning, 2012)
Book Description: Since 1938, the Milady Standard Cosmetology has been the premier textbook for Cosmetology education. Each subsequent edition has evolved with the changing styles of the era while maintaining a firm foundation in the basic procedures and applications of beauty culture that have endured for generations. Building upon the strong pedagogical features of previous editions, the Milady Standard Cosmetology 2012 is vibrant and colorful to capture the visual learner's interest and focus their attention on the subject matter which is the cornerstone of their education. The Milady Standard Cosmetology 2012 textbook takes advantage of the most sophisticated methods for relaying information, stimulating thought, aiding comprehension, and enhancing retention. This new edition contains a completely revised section on infection control principles and practices, new procedures, and revised and updated chapters written by industry experts, as well as step-by-step procedures demonstrated specifically for left-handed individuals. Educators and students have access to over twenty instructor tools and student supplements which greatly increase the chances for student success and make lesson planning simple. Each supplement has been tailored to fit the exact needs of the cosmetology student and match the changes made to the new edition. The Milady Standard Cosmetology 2012 is the basis for your students' success during their education and will continue to be a valuable resource as they progress through their careers.
Part 4: Skin Care: -- Hair removal: -- Why study hair removal? -- Client consultation -- Contraindication for hair removal -- Permanent hair removal -- Temporary hair removal -- Procedures -- Facials: -- Why study facials? -- Skin analysis and consultation -- Determining skin type -- Skin care products -- Client consultation -- Facial massage -- Facial equipment -- Electrotherapy and light therapy -- Facial treatments -- Aromatherapy -- Procedures -- Facial Makeup: -- Why study facial makeup? -- Cosmetics for facial makeup -- Makeup color theory -- Basic professional makeup application -- Special-occasion makeup -- Corrective makeup -- Artificial eyelashes -- Procedures -- Part 5: Nail Care: -- Manicuring: -- Why study manicuring? -- Nail technology tools -- Professional cosmetic products -- Basic manicure -- Man's manicure service -- Massage -- Spa manicures -- Aromatherapy -- Paraffin wax treatments -- Nail art -- Only the beginning -- Procedures -- Pedicuring: -- Why study pedicuring -- Pedicure tools -- About pedicures -- Disinfection -- Procedures -- Nail tips and wraps: -- Why study nail tips and wraps? -- Nail tips -- Nail wraps -- Nail wrap maintenance, repair, and removal -- Procedures -- Monomer liquid and polymer powder nail enhancements: -- Why study monomer liquid and polymer powder nail enhancements? -- Monomer liquid and polymer powder nail enhancements -- Monomer liquid and polymer powder nail enhancement supplies -- Monomer liquid and polymer powder nail enhancement maintenance, crack repair, and removal -- Odorless monomer liquid and polymer powder products -- Colored polymer powder products -- Procedures -- UV gels: -- Why study UV gels -- UV gels -- UV gel supplies -- When to use UV gels -- Choosing the proper UV gel -- UV light units and lamps -- UV gel polish -- UV gel maintenance and removal -- Procedures -- Part 6: Business Skills: -- Seeking employment: -- Why study how to prepare for and seek employment? -- Preparing for licensure -- Preparing for employment -- Job interview -- On the job: -- Why study what is like on the job? -- Moving from school to work -- Out in the real world -- Managing your money -- Discover the selling you -- Keeping current clients and expanding your client base -- On your way -- Salon business: -- Why study the salon business? -- Going into business for yourself -- Operating a successful salon -- Building your business -- Appendix A: Associations -- Appendix B: Metric conversions -- Glossary/Index.
Rev. ed. of: Milady's standard cosmetology. 1998.
Includes index.
Keywords: Beauty culture; Beauty culture